Adsorption of nonionic surfactant mixtures at the hydrophilic solid-solution interface. - Penfold, J; Tucker, I; Thomas, R (2005)
The adsorption of the mixed nonionic surfactants, monododecyl triethylene glycol (C2EO3) and monododecyl octaethylene glycol (C12EO8), at the hydrophilic silica-solution interface has been studied by specular neutron reflectivity. The adsorption at the solid-solution interface is compared with that previously measured at the air-solution interface. The marked differences that are observed are explained in terms of the different packing constraints or preferred curvature arising from the disparity in the respective headgroup dimensions.